Violência e criminalidade na ditadura civil-militar (1964-1985): representações do periódico maranhense Jornal Pequeno - Souza, Lenia Fernanda de Oliveira (2016)
This study aims to analyze representations of aspects linked to violence and criminality produced in Maranhão Jornal Pequeno journal during the civil-military dictatorship (1964-1985), with the spatial cutout of the city of Sao Luis. To this end, we first made a contextualization effort of the scenario involving the problems of violence and ciminality in Brazil during the dictatorship, as we seek to rebuild the newspaper's trajetory in question during this same period. other than copies of the paper, oral reports provides by journalists connected in some way to this newspaper constituted in primary sources for understanding both the periodic trajectory analyzed the for news built on it. Specifically, the analysis focused on presenting representations constructed in the journal about crimes and criminals, public security policies and police violence, trying to understand, yet, changes and / or continuities in discourses daily conveyed by it. The analysis also point out how this newspaper was inserted in the debate on urban violence that has expanded in the country at the very moment of political openness.